The significance and insignificance of Clive Bell’s formalism1 - Snyman, Johan (Koers, 1993)
Clive Bell coined the phrase significant form. The way he initially defined the phrase and the way he implemented it were two different matters. In this article Bell's procedure is analysed as a characteristic of late modernist aesthetics, i.e. an attempt to come to terms with the challenge of the radically new in art. It is suggested that one should bear in mind that formalism in this sense is a theory of artistic material which explains how meaning is communicated and perceived through non-discursive qualities of the artistic material. That is the relevance of Susanne K. Longer's reinterpretation of Bell's phrase.